The Natural Resource Degradation and Vulnerability Nexus : An Evaluation of the World Bank’s Support for Sustainable and Inclusive Natural Resource Management (2009–19) - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Many of the world’s poor people depend on natural resources for their well-being. Four-fifths of the world’s poor people live in rural areas, and most rural poor people depend on natural resources for their livelihoods. The renewable natural resources on which poor people depend are increasingly being degraded, posing significant risks to resource-dependent communities. The World Bank has committed to reducing the vulnerability of resource-dependent people. This evaluation assesses how well the World Bank has addressed natural resource degradation to reduce the vulnerabilities of resource-dependent people.